Design and evaluation of single-stand chairless exoskeleton for standing and sitting tasks - Halim, Isa; Abdullah, Zulkeflee; Mahadzir, Muhammad Nadzirul Izzat; Zainal Abidin, Muhammad Zaimi; Md Ghazaly, Mariam; Adi, Saptari (Taylor's University, 2024)
With the advancement of assistive technology, numerous chairless exoskeletons have emerged in the market, enabling users to perform tasks in standing and sitting postures. However, design information of the chairless exoskeletons, particularly on the structural strength, user's muscle contraction, contact pressure and usability, are scarce, which influences the user acceptance of the devices. This study aimed to determine the user's requirements and develop a single-stand chairless prototype exoskeleton. The prototype was compared to a double-stand chairless commercial exoskeleton to evaluate its mechanical compression strength, muscle contraction, contact stress, and system usability scale (SUS). A questionnaire survey was performed among 103 operators of manufacturing industries to determine the user's requirements for a chairless exoskeleton. Ten subjects participated in muscle contraction, contact pressure, and SUS studies. A chairless exoskeleton's most required design feature was 'ease of use.' Muscle assessment quantified a significant reduction of contraction in the lower limb muscles (P-value < 0.05) when wearing the single-stand chairless prototype exoskeleton. Furthermore, the contact pressure under the thighs was eliminated when sitting on the single-stand chairless prototype exoskeleton. The usability study revealed an average SUS of 79.5, defining a better usability of the single-stand chairless prototype exoskeleton, compared to a SUS of 67.3 for the double-stand chairless commercial exoskeleton. The authors concluded that the single-stand chairless prototype exoskeleton effectively minimises muscle fatigue and contact stress as well as improves usability for sitting and standing tasks. This comprehensive design information is undoubtedly helpful for designers to improve user acceptance of the devices in industrial applications.